Analysis of Self-Care Behavior Factors Among Patients with Hypertension at the Rasau Jaya Community Health Center in 2025 - Dedi Alamsyah; Selviana Selviana; Linda Suwarni (Ahmar Metastasis Health Journal, 2026)
Hypertension, known as “The Silent Killer,” is a global health challenge with an ever-increasing prevalence. In the service area of the Rasau Jaya Community Health Center, 5,662 cases were recorded from January through October 2025. Management of this chronic disease relies heavily on self-care behavior. This study aims to analyze factors associated with self-care behavior among patients with hypertension at the Rasau Jaya Community Health Center in 2025. A quantitative analytical study with a cross-sectional design was conducted from June to October 2025. A sample of 252 respondents was selected using purposive sampling from the population of patients with hypertension. Data were analyzed univariately and bivariately using the Chi-Square test (α=0.05; CI=95%). The results showed that the majority of respondents with good self-care behaviors were in the 31–44 age group (94.7%), male (78.3%), highly educated (93.7%), had a family history (82.9%), and had been living with the condition for >5 years (89.1%). However, the majority of respondents had knowledge and self-efficacy levels in the “poor” category (83.3%). Bivariate analysis showed a significant association between family history (p=0.009; PR=1.20) and duration of hypertension (p=0.026; PR=2.41) with self-care behavior. The variables of age, gender, educational level, knowledge level, and self-efficacy did not show statistically significant associations. In conclusion, family history and duration of hypertension are factors associated with self-care behavior in patients with hypertension. Patients are recommended to improve self-management through family support for home care and by regularly participating in the Prolanis program at community health centers to maintain long-term treatment motivation.